In-tube gel electro-membrane combined with microfluidic paper-based device: A green and miniaturized extraction mode for the chromium speciation - Hadi Tabani; Thidarat Samkumpim; Waleed Alahmad; Farzaneh Dorabadizare; Pakorn Varanusupakul (Advances in Sample Preparation, 2022)
For the first time, in-tube gel electro-membrane microextraction (IT-G-EME) system followed by microfluidic paper-based analytical devices (µPADs) as a low-cost reading platform was fabricated for the speciation of trivalent chromium (Cr(III)) and hexavalent chromium (Cr(VI)) as model cationic and anionic compounds. In this new miniaturized extraction mode, a transparent narrow-bore polymeric tube was used as housing of the aqueous acceptor phase (AP, 30 µL), while an agarose gel membrane was placed as a micro plug (2.5 mm) at the beginning of the tube. A circular shape vial (1.5 mL, pH 5.5) containing chromium species as donor phase (DP) was connected between two tubes which previously filled with gel membrane and aqueous AP. By applying electric potential, the positively charged Cr(III) and negatively charged Cr(VI) in the DP migrated selectively toward cathodic and anodic tubes, respectively. After extraction, each AP was analyzed by µPAD, which had already been modified with diphenylcarbazide (DPC). Under the optimized extraction conditions, a good limit of detection (LOD) equal to 7.0 µg L–1 was achieved for both analytes, while the extraction recoveries for Cr(VI) and Cr(III) were 72% and 84%. In addition, the developed approach was used for the quantification of chromium species in water samples.